Android-based car parking monitoring system - Mohd Izzat Syahmi, Saiful Azman (2019)
The increasing number of vehicles on the road today can cause of traffic jammed since vehicle is a basic necessity used by all people. As the growth number of vehicles usage, the needs of car parking lot also will be limited and will be a problem for user to find a parking space especially in shopping mall. Technologies as Internet of Thing (IoT) is a system of interrelated computing devices with ability to transfer data over a network without requiring human-to-human or human-to-computer interaction being are utilized in almost every kind of fields in today society. In the context of this work, a mobile application for user is developed to facilitate in finding a specific parking space. Android-based Car Parking Monitoring System is capable to provide a user to review the available parking space and find the nearest parking from current user location with sensor equipped to detect incoming and outgoing cars from parking space in the mall. Therefore, with the simple and user-friendly interface presented, user can easily understand and use this mobile application to explore the parking space. Finally, this study explored the used of Internet of Thing technology in real environment for the purpose of movement detection and location service to notify the user that has been visualized in mobile application.